Examining Islam as a System for Peace-Building and Co-Existence - Farhat Aziz; Razia Shabana; Farida Yousuf (Pakistan Journal of Islamic Research)
This research is about the examining Islam as a system for peace-building and co-existence. Allāh has created this universe on the basis of peace, and co-ordination. The purpose of this creation is that human beings can inculcate peace-building and harmony with full charms and colors. Islam has provided a solution for the whole world to establish peace, and co-ordination in the world.  The basic Islamic rule is to create such a world in which human beings forget their problems and hardships of their sordid real life and try to lead a peaceful and harmonious life. Islam helps the man to shed his personal discriminations and deals with tolerating, respect other’s views, ideas, liking and dis-likings to face diversity. Islam promotes piety, goodwill, sympathy, tolerance, and groom human personality to eradicate evils such as wrath, bloodshed, cruelty, barbarism, and savageness. A true Muslim cannot even think evil for others rather he will prove himself the most beneficial, helpful and tolerate person among other people in every aspect of his life i.e: moral, social, economic and political etc. Islam imposes many responsibilities upon the Muslim in order to develop a universal harmonious society so that human beings can lead a life that fulfills Allāh’s demands on them. Islam compels believer to demonstrate tolerance for peace-building, co-ordination, and co-existence in their lives so that they can encounter the evils, adversities, and cruelties of life which can weaken belief and distract the believers from the right path.